Evaluation of the Water Ambulance Service Program at the Health Crisis and Emergency Center Province Health Office of DKI Jakarta in 2023 - Eka, Shella Cahya; Sari, Kurnia (Journal of Indonesian Health Policy and Administration, 2024)
The high demand for ambulance services at the 119 Public Safety Center of the DKI Jakarta Health Office, including in the Administrative District of the Kepulauan Seribu, highlights the importance of providing water ambulances. This study aims to analyze the implementation of the Water Ambulance Service by the DKI Jakarta Health Office using the Context, Input, Process, Product (CIPP) program evaluation approach. Using a qualitative approach, primary and secondary data were collected through observations, in-depth interviews, and document review. The findings show that implementing the Water Ambulance Service aligns with the context, objectives, and targets of the DKI Jakarta Health Office's vision, mission, and strategic plan. However, several input aspects of the Water Ambulance still need to be improved in terms of quantity, competence (for human resources), and quality, which somewhat hinder the Water Ambulance services. Additionally, the service still needs to run smoothly due to the non-integration of the program system with the system that provides health personnel, particularly nurses and midwives. It is hoped that the DKI Jakarta Government will review and issue policies regarding the optimization of health service facilities, especially in Kepulauan Seribu region, regulations for an integrated system for land and water ambulances, and the establishment of service rates for water ambulances in the Administrative District of Kepulauan Seribu.